Transmission Electron Microscopy Studies of Cellular Responses to Entry of Virions: One Kind of Natural Nanobiomaterial - Zheng Liu; Shuyu Liu; Jinming Cui; Yurong Tan; Jian He; Jingqiang Zhang (International Journal of Cell Biology)
Virions are one kind of nanoscale pathogen and are able to infect living cells of animals, plants, and bacteria. The infection is an intrinsic property of the virions, and the biological process provides a good model for studying how these nanoparticles enter into cells. During the infection, the viruses employ different strategies to which the cells have developed respective responses. For this paper, we chose Bombyx mori cypovirus 1 (BmCPV-1) interactions with midgut cells from silkworm, and severe acute respiratory syndrome (SARS) associated coronavirus interactions with Vero E6 cells, as examples to demonstrate the response of eukaryotic cells to two different types of virus from our previous studies. The bacteriophage-bacteria interactions are also introduced to elucidate how the bacteriophage conquers the barrier of cell walls in the prokaryotic cells to transport genome into the host.